Analisis Penerapan Akuntansi Aset Tetap Terhadap Pernyataan Standar Akuntansi Keuangan No. 16 Pada PT Shanti Adventure Tour - Ni Putu Diah Utari; I Putu Fery Karyada; I Made Endra Lesmana Putra (Hita Akuntansi dan Keuangan, 2023)
Fixed assets have an important role in business. To support a business in the progress of the company, equipment or equipment is needed which is one part of fixed assets. Errors in valuation, calculation and presentation of fixed assets will affect the company's financial statements. This study aims to assess the extent to which the company has implemented fixed asset accounting policies in accordance with applicable standards, namely PSAK No. 16 regarding fixed assets. The research method used is descriptive analysis method with a qualitative approach. From the results of the study it can be concluded that PT Shanti Adventure Tour in carrying out its accounting activities is guided by company policies that are in accordance with PSAK No. 16. In terms of recognition, measurement, and disposal of fixed assets are in accordance with PSAK No. 16. However, there are still errors in the application of the method depreciation and presentation of fixed assets at PT Shanti Adventure Tour. Keywords: fixed asset, psak no.16